Developing a fluorometric urease activity microplate assay suitable for automated microbioreactor experiments - Lapierre, Frédéric M.; Bolz, Isabel; Büchs, Jochen; Huber, Robert (Frontiers in Bioengineering and Biotechnology, 2022)
Quantifying urease activity is an important task for Microbial Induced Calcite Precipitation research. A new urease activity microplate assay using a fluorescent pH indicator is presented. The method is also suitable for automated measurements during microbioreactor experiments. The assay reagent consists of the green fluorescent pH-indicator fluorescein, urea and a phosphate buffer. After sample addition, the microbial urease hydrolyses urea, which results in a pH and hence fluorescence increase. The fluorescence signal can be measured with a microplate reader or with the microbioreactor system BioLector, allowing for automated urease activity measurements during cultivation experiments. In both measurement systems, the fluorescence signal slope highly correlates with the urease activity measured offline with standard methods. Automated measurement is possible, as no sample preparation such as centrifugation or adjusting of the optical density is required. The assay was developed so that the culture samples turbidity, salinity or buffer concentration does not have a negative impact on the fluorescence signal. The assay allows for straightforward, non-hazardous, parallelized, cheap and reliable measurements, making research on ureolytic bacteria for Microbial Induced Calcite Precipitation more efficient. The assay could be adapted to other enzymes, which have a strong impact on the pH value.